Efficacy of ZM16 10 (Bacillus amyloliquefaciens DSM 25840) as a feed additive for weaned piglets and minor porcine species. (13th November 2019) - ,; Bampidis, Vasileios; Azimonti, Giovanna; Bastos, Maria de Lourdes; Christensen, Henrik; Dusemund, Birgit; Kouba, Maryline; Kos Durjava, Mojca; López‐Alonso, Marta; López Puente, Secundino; Marcon, Francesca; Mayo, Baltasar; et al.
Abstract: Following a request from the European Commission, the Panel on Additives and Products or Substances used in Animal Feed (FEEDAP) was asked to deliver a scientific opinion on the efficacy of ZM16 10 for weaned piglets and minor porcine species. The additive is a preparation containing viable spores of a strain of Bacillus amyloliquefaciens (DSM 25840). This product is available in two forms, ZM16 and ZM16 10, which contain the bacterium in concentrations of 1.25 × 10 9  CFU/g additive and 1.25 × 10 10 CFU/g additive, respectively. In a previous opinion, the FEEDAP Panel assessed the safety and the efficacy of the product when used in weaned piglets. The Panel concluded that the active agent fulfils the requirements of the qualified presumption of safety (QPS) approach to the assessment of safety. Consequently, the additive is presumed safe for the target animals, consumers of products from animals fed with the additive and the environment. Regarding the safety for the user, the FEEDAP Panel could not conclude on the potential of the additive to be irritant to skin and eyes or its dermal sensitisation due to the lack of data. However, it concluded that the additive should be considered a potential respiratory sensitiser. The data provided in the previous assessment to support the efficacy of the additive was not sufficient to conclude on the efficacy of the additive in weaned piglets or minor weaned porcine species. The applicant provided supplementary information to complement the data, including a statistical analysis pooling data from different studies. Based on the newly submitted data, the Panel concluded that the additive has a potential to be efficacious as a zootechnical additive in weaned piglets at a level of 5 × 10 8 CFU/kg complete feed or in water for drinking at 1.7 × 10 8 CFU/L. This conclusion was extrapolated to minor porcine species at the same developmental stage.